The Small GTP‐Binding Protein Rhes Influences Nigrostriatal‐Dependent Motor Behavior During Aging. Issue 4 (8th February 2016) - Pinna, Annalisa; Napolitano, Francesco; Pelosi, Barbara; Di Maio, Anna; Wardas, Jadwiga; Casu, Maria Antonietta; Costa, Giulia; Migliarini, Sara; Calabresi, Paolo; Pasqualetti, Massimo; Morelli, Micaela; Usiello, Alessandro
ABSTRACT: Background: Here we aimed to evaluate: (1) Rhes mRNA expression in mouse midbrain, (2) the effect of Rhes deletion on the number of dopamine neurons, (3) nigrostriatal‐sensitive behavior during aging in knockout mice. Methods: Radioactive in situ hybridization was assessed in adult mice. The beam‐walking test was executed in 3‐, 6‐ and 12‐month‐old mice. Immunohistochemistry of midbrain tyrosine hydroxylase (TH)–positive neurons was performed in 6‐ and 12‐month‐old mice. Results: Rhes mRNA is expressed in TH‐positive neurons of SNpc and the ventral tegmental area. Moreover, lack of Rhes leads to roughly a 20% loss of nigral TH‐positive neurons in both 6‐ and 12‐month‐old mutants, when compared with their age‐matched controls. Finally, lack of Rhes triggers subtle alterations in motor performance and coordination during aging. Conclusions: Our findings indicate a fine‐tuning role of Rhes in regulating the number of TH‐positive neurons of the substantia nigra and nigrostriatal‐sensitive motor behavior during aging. © 2016 International Parkinson and Movement Disorder Society